Perlindungan Hukum Anak Lahir di Luar Nikah Perspektif Hukum Islam dan Hukum Positif - Imani, Andra Ahmad; Islam ZH, M. Rasikhul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The increasing cases of women becoming pregnant before marriage has resulted in many children being abandoned due to irresponsible parents. Islam and positive law are currently deemed ineffective in implementing legal objectives. Thus, it is important for this research to be carried out so that it can answer legal questions. This research aims to determine the legal protection of children born out of wedlock in terms of Islamic law and positive law. This research uses normative legal research with a legal and conceptual approach, the sources of legal materials used are primary, secondary and tertiary legal materials with literature review methods sourced from the Al-Quran and Hadith, books, government regulations and other things that are related. From the analysis described in this research, the conclusions reached are: 1) in Islamic law it is stated that children born out of wedlock have no lineage with their biological father, but the child still has rights which include, the right to life, care, proper education and the right to livelihood. . 2) In positive law, children born out of wedlock also have the same legal protection rights as children in general. 3) It is felt that the state has not been optimal in handling the issue of the rights of children born out of wedlock. It appears that there has been no response from State Institutions regarding changes to the Marriage Law, but only changes in the marriage age. Meanwhile, children born out of wedlock are not taken into consideration in changing the law.